A new approach for selecting best resources nodes by using fuzzy decision tree in grid resource broker - Bouyer, Asgarali (Science and Engineering Research Support Society (SERSC), 2008)
Nowadays, Grid Computing has been accepted as an infrastructure to perform parallel computing in distributed computational resources. Grid has users, resources, and an information service (IS). Resource broker service is one of the main services in grid to find resources, filter resources, allocate resources, etc. Resource selection is part of resource broker that is an important issue in a grid environment where a consumer and a service provider are distributed geographically. In this paper, we design and implement a new data mining –based Grid resource broker service for selection resources on grid environment. The role of this resource broker service is using learning method to find the best nodes according to the requirements of the job and the distributed computing resources on the Grid. The provided application can be executed on top of Globus Toolkit (GT) middleware. The results of experiments show a strong effect in improving resource finding cycle